Orthodontic treatment need among young Saudis attending public versus private dental practices in Riyadh - Al-Jobair AM; Baidas LF; Al-Hamid AA; Al-Qahtani SG; Al-Najjar AT; Al-Kawari HM (Dove Medical Press, 2016)
Asma M Al-Jobair,1,2 Laila F Baidas,1,2 Anfal A Al-Hamid,2 Sara G Al-Qahtani,2 Amani T Al-Najjar,2 Huda M Al-Kawari1,2 1Department of Pediatric Dentistry and Orthodontics, 2College of Dentistry, King Saud University, Riyadh, Saudi Arabia Objective: To assess and compare the severity of malocclusion and orthodontic treatment need among young Saudis receiving free treatment at public dental practices versus those paying for treatment at private practices. Materials and methods: This retrospective study evaluated the records of 300 patients (179 females, 121 males; age 13–21 years) treated at orthodontic clinics from 2013 through 2015. The public sample was selected from orthodontic clinics at the College of Dentistry, King Saud University (KSU); the private sample was selected from five private orthodontic clinics in Riyadh, Saudi Arabia. The records were examined for the severity of malocclusion and for orthodontic treatment need using the Dental Health Component of the Index of Orthodontic Treatment Need. The prevalence of each occlusal discrepancy and the Dental Health Component grade were recorded. The severity of malocclusion and orthodontic treatment need were compared between practice types, age groups, and sexes with the chi-square test. Results: Displacement, increased overjet, and Class II and III malocclusion were the most common orthodontic problems in this study. Patients attending public clinics at KSU generally had more severe malocclusion than the patients attending private clinics. Seventy-seven percent of orthodontically treated patients at KSU clinics were in great need of treatment, compared with 58.5% of patients treated at private clinics (P=0.003). Among the patients with great treatment need, approximately 62% of male patients and 70% of patients ≤16 years of age were treated at KSU clinics, compared with 38% and 48%, respectively, treated at private clinics (P<0.0001). Conclusion: Young Saudis receiving free orthodontic treatment at public clinics at KSU had more severe malocclusion with greater need of orthodontic treatment than the patients paying for treatment at private clinics. Keywords: malocclusion, orthodontic treatment need, IOTN, public, private